THE USE OF TOTAL PHYSICAL RESPONSE METHOD IN TEACHING VOCABULARY AT JUNIOR HIGH SCHOOL IN CIMAHI - Atin Atin Supriyatin; Ningtyas Orilina Argawati (PROJECT (Professional Journal of English Education), 2021)
This study aims to improve Vocabulary mastery skills using Total Physical Response Method,the low Vocabulary mastery of eight grade in junior high school is caused by two factors,namely run short of understanding of the significancy of Vocabulary by reason of slight of Vocabulary that is owned,then the difficulty of students speaking in English,because of the scant of Vocabulary they have so they are confused when speaking.this study uses descrivtipe qualitative method. the responden of the study is the eight graders of SMP in Cimahi, the total of 33 students with specifications male 21 students and female 12 students. the author pick sampling jenuh on probability sampling.the instruments used were observation sheet,questionnaire,interview and test.data gain out of the instruments that have been used are interview ,observation sheet,questionnaire and tests.the results showed that the Total Physical Response Method was effectively applied in studying Vocabulary because after applied the Total Physical Response Method in the learning process there was an increase in understanding of the signifiance of Vocabulary as well as an increase in student motivation and creativity in following the learning process, and the test outcome of the tests given were satisfactory because the average get a minimum score of 80 and a maximum of 97 with KKM 75.with the accomplishment of these values could be said the use of the Total Physical Response Method can help improve students’ Vocabulary mastery.Keywords: Vocabulary, Total Physical Response Method